An Improved Solar Cooling System for Date Safety and Storage under Climate of the Maghreb - Afif, Benameur; Merabet, Boualem; İnç, Mustafa; Menni, Younes; Alsharif, Sameer; Althobaiti, Ahmed; Aly, Ayman A. (Wiley, 2022)
As a freely available energy source for managing long-term issues in energy crisis, solar energy (SE) will have to grow more to meet world's energy demands. Maghreb countries have launched international tenders for large-scale solar power projects, confirming north African countries' goals to become green-power leaders, by enforcing renewable energy development policies. This work is aimed at simulating and designing a SE cooler to safely store quality and tasty dates. By optimizing the storage parameters and cooling gas with less energy consumption, R152a has been confirmed as a reliable refrigerant to own high critical temperature, sufficient specific heat capacity, and potential cost-effectiveness of compression. Safe packaging in Tolga-Algeria-Dates food company can be achieved by safe cooling systems that is aimed at wide variation of energy storage and delivery requirements of the manufacturing process. The performance ratio (PR) and energy losses have been analyzed by using the PVsyst software. The paper is also aimed at studying load requirements of an SE cooler of dates, designing/installing a standalone solar PV system, and modeling the refrigerant gas of the SE cooler, done with INTARCON software and SOLKANE refrigerant software program. PR and loss analysis has been done using PVsyst. Total amounts of yearly energy injected into grid and nominal PV array energy are estimated to be, respectively, 84.536 and 85.861 MWh, while total yearly losses of the system are estimated to be 15.5 MWh. It reveals that the PV system efficiency set from ~10% in winter to 11.3% in summer, while PR rises from a 77.5% in July to 89.3% in December. Future research will design of energy consumption monitoring of the PV system, favoring SE cooling of dates. Via PVsyst concrete realities of PV performance and insights for better operational monitoring were well understood.
Keywords: Thermal-Energy Storage; Water Pumping Systems; Environmental Impacts; Buildings; Refrigeration; Requirements; Temperature; Performance; Challenges; Countries